Developing and maintaining practical archives : - Hunter, Gregory S (Neal-Schuman Publishers, 2003)
The book presents a text for archival educators and students. It discusses everything from undertaking a records survey to issues involved in electronic archives. This revised edition features new material on international perspectives on appraisal, refinements to U.S. theories on selection and appraisal, dealing with Encoded Archival Description and the Internet, updated information on security and disaster planning, the Digital Millennium Copyright Act, the Sonny Bono on archival management, and the archival profession